FRACTAL ECONOMY FUNCTIONS: COGNITIVE AND PARTICIPATION - Michael Barnsley (Investigación Administrativa, 2012)
In this paper we present fractal modeling that will help us understand and analyze the prospects of reaching the stations listed its shares in the financial market and the correlation of the latter with the company, including relaxation of the ranges we purchase and sales functions sine and cosine to serve as basis for investment circles via fractal Fibonacci series is non-parametric statistics with golden mean.